JENIS MAKNA DAN PERUBAHAN MAKNA - Muzaiyanah Muzaiyanah (Wardah, 2012)
Meaning is an integral part of the semantics and always sticks of what we Tell the. Meaning, a form of language that should be analyzed within the boundaries of the critical elements in a situation where speakers mengujarnya. Change of meaning is a shift in the meaning of the first to sense the next one, which extends, narrows, total change, refinement, and coarsening. Reasons for changing the meaning, the development of science and technology, social and cultural development, the development of the field of use, the association, exchange sensation, different responses, and the abbreviation.